Héritages coloniaux Les Suisses d'Algérie - Fois, Marisa (Présent et histoire, 2021)
What relationship do European countries have with their colonial past? The way they deal with, reread, reconstruct, forget or conceal this part of their history is decisive for understanding today's geopolitics and for questioning current societies. The Confederation, under its cloak of neutrality, has long denied its involvement in colonial processes. However, the Swiss participated in the settlement of French Algeria, where they exercised forms of domination, notably through private investments. When Algerian independence was proclaimed, the Confederation faced the delicate task of organising the 'return' of Swiss settlers. Following nationalisations and expropriations overseas, property had to be protected, and pensions paid. This book offers valuable tools for understanding colonial history in a decolonised world. Supported by Swiss, French, Italian and English archival sources − most of which have never been published before − this study reconstructs the interplay of scales and highlights the decisive role of the Association des Suisses spoliés d'Algérie ou d'outremer